HUBUNGAN KEBUGARAN JASMANI TERHADAP PRESTASI AKADEMIK SISWA (STUDI PADA KELAS XI MAN MOJOSARI) - ACHMAT, FADLY (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Physical fitness is someone body ability to perform daily activity maximally, whereas they still able to perform other additional activities without experience significant exhaustness. Physical fitness extremely needed by student to perform learning activity whether at class or outclass. Everyday student perform learning activity starting from morning to evening. Students try to obtain good academic achievement. This study aim to knowing the relation between physical fitness to academic achievement of eleventh grade student of MAN Mojosari. The type of research is quantitative research and apply product moment correlation. The object of this research student of MAN Mojosari. The study population was all students in class XI MAN Mojosari totaling 281 students. By using cluster random sampling samples selected at random 2 classes ie class XI Religion and class XI Science 3 as many as 57 students were tested using the test MFT. Free variable of this research is physical fitness that can be detect by MFT test while bounded variable is academic achievement that can be detected from odd semester report score school year 2012-2013. While to analyze data in this research using data analysis technique SPSS version 16.0. Based on data analysis that apply SPSS 16.0 obtain correlationas big as -0.281. It mean that there is a relation between physical fitness with student academic achievement. Negative sign in a matter of correlation means that the higher the students' physical fitness declining student achievement outcomes class XI MAN Mojosari. This is because the majority of students who take the class XI many school programs, namely, extracurricular activities, activities of Intra-School Students Organization (OSIS), and activities outside of school that could lead to decline in student academic achievement. Thus, from this study it can be detected that there is a relation between physical fitness with education achievement eleventh grade student of MAN Mojosari school year 2012-2013.  Keywords: physical fitness to academic achievement